Cereal Genomics - Gupta, P. K.; Varshney, R. K.; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2005)
Cereals make an important component of daily diet of a major section of human population, so that their survival mainly depends on the cereal grain production, which should match the burgeoning human population. Due to painstaking efforts of plant breeders and geneticists, at the global level, cereal production in the past witnessed a steady growth. However, the cereal production in the past has been achieved through the use of high yielding varieties, which have a heavy demand of inputs in the form of chemical fertilizers, herbicides and insecticides/pesticides, leading to environmental degradation. In view of this, while increasing cereal production, one also needs to keep in mind that agronomic practices used for realizing high productivity do not adversely affect the environment. Improvement in cereal production in the past was also achieved through the use of alien genetic variation available in the wild relatives of these cereals, so that conservation and sustainable use of genetic resources is another important area, which is currently receiving the attention of plant breeders. The work leading to increased cereal production in the past received strong support from basic research on understanding the cereal genomes, which need to be manipulated to yield more from low inputs without any adverse effects as above. Through these basic studies, it also became fairly apparent that the genomes of all cereals are related and were derived from the same lineage, million of years ago.
Cereal Genomics: An Overview -- Molecular Marker Systems and Their Evaluation for Cereal Genetics -- Molecular Maps in Cereals: Methodology and Progress -- Organization of Retrotransposons and Microsatellites in Cereal Genomes -- Comparative Genomics in Cereals -- Population Genetic Structure of Wild Barley and Wheat in the Near East Fertile Crescent: Regional and Local Adaptive Patterns -- Gene and Genome Changes During Domestication of Cereals -- QTLs and Genes for Disease Resistance in Barley and Wheat -- QTLs and Genes for Tolerance to Abiotic Stress in Cereals -- Marker Assisted Selection in the Cereals: The Dream and the Reality -- Map-Based Gene Isolation in Cereal Genomes -- Gene Distribution in Cereal Genomes -- Whole Genome Sequencing: Methodology and Progress in Cereals -- Bioinformatics and Triticeae Genomics: Resources and Future Developments -- Functional Genomics of Seed Development in Cereals -- Functional Genomics for Tolerance to Abiotic Stress in Cereals -- The Arabidopsis Genome and Its Use in Cereal Genomics -- Rice Genome as a Model System for Cereals -- Cereal Genomics Research in the Post-genomic Era -- Genomics for Cereal Improvement.
Keywords: Life sciences; Human genetics; Genetic engineering; Agriculture; Evolutionary biology; Plant science; Botany; Life Sciences; Agriculture; Genetic Engineering; Human Genetics; Plant Sciences; Evolutionary Biology; Electronic books